NOTE ON A SUPERNOVA IN A SAN LUIS POTOSIIRAL GALAXY - HARO, G (UNAM, Observatorio Astronómico Nacional, CD MEXICO, DF, MEX, 1959)
From the comparison of plates taken in 17-18 Nov 1955 and 14-15 November 1957 we identified a 15.7 magnitude supernova at 0h 44.8m and -17°11'.
BOL OBS TONAN TACUB
Keywords: NOTE, SUPERNOVA, SPIRAL GALAXY; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; GALAXIAS